PENGARUH UPAH DAN PENDAPATAN ASLI DAERAH TERHADAP PERTUMBUHAN EKONOMI KABUPATEN / KOTA DI JAWA TIMUR TAHUN 2011-2015 - Chandralecha Rahmatus Amelia; Dwi Susilowati; Sudarti Sudarti (Jurnal Ilmu Ekonomi JIE, 2019)
This study aims to determine the economic growth, wages and local revenue in East Java Year 2011-2015. The type of research used in this study is to use descriptive quantitative research.The analysis tool used in this research is using regression panel data analysis method. Based on the result of regression analysis of panel data obtained t test result (partial test) showing that wage variable (X1) has positive and significant effect to Economic Growth (Y), which means if Wage is higher, then economic growth will increase, Local Revenue has a positive and significant impact on Economic Growth (Y) in East Java, which means if the Revenue of the Region increases then Economic Growth will increase. Simultaneously F statistic value 1210,824 is bigger than F table 2,42, this means Ho is rejected and H1 accepted. Based on the results of this study, it is necessary to review the existence of the impact of the existence of the influence of Local Revenue and Income (PAD) on Economic Growth in East Java Year 2011-2015 in order to increase economic growth in East Java maximally..